2016
DOI: 10.1136/tobaccocontrol-2016-053146
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the logic and framing of a tobacco industry campaign opposing standardised packaging legislation in New Zealand

Abstract: BATNZ's Agree-Disagree campaign relied on unsound arguments, logical fallacies and rhetorical devices. Given the industry's frequent recourse to these tactics, we propose strategies based on our study findings that can be used to assist the tobacco control community to counter industry opposition to standardised packaging. Greater recognition of logical fallacies and rhetorical devices employed by the tobacco industry will help maintain focus on the health benefits proposed policies will deliver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…This would helpfully supplement existing analyses of tobacco industry arguments which have drawn mainly on public consultation data and advertisements. [19, 3335, 68] This deficit could be addressed in future studies by comparatively analysing pre-identified industry-linked Twitter profiles and content, using a method similar to that of Kavuluru & Sabbir’s (2016) work on e-cigarettes[69]. This approach could also add to existing literature [19, 34] by unearthing previously hidden relationships between tobacco companies and supposedly independent third-parties and could also be extended to other health-harming industries, such as alcohol and sugar-sweetened beverage producers and retailers.…”
Section: Discussionmentioning
confidence: 99%
“…This would helpfully supplement existing analyses of tobacco industry arguments which have drawn mainly on public consultation data and advertisements. [19, 3335, 68] This deficit could be addressed in future studies by comparatively analysing pre-identified industry-linked Twitter profiles and content, using a method similar to that of Kavuluru & Sabbir’s (2016) work on e-cigarettes[69]. This approach could also add to existing literature [19, 34] by unearthing previously hidden relationships between tobacco companies and supposedly independent third-parties and could also be extended to other health-harming industries, such as alcohol and sugar-sweetened beverage producers and retailers.…”
Section: Discussionmentioning
confidence: 99%
“…This is unsurprising given online media is not currently restricted by tobacco regulations. An example of this was seen in British American Tobacco (BAT) New Zealand’s online media campaign ‘Agree–Disagree’, which was launched to undermine the New Zealand government’s plain packaging consultations 3. Given TTCs’ aggressive record of undermining tobacco control policies,2–5 bidding for political support,17 continuing advertising and promotion through covert means18–21 and long-standing history of attempting to improve their image through CSR activities,6 it is important to monitor the content being published by TTCs on social media.…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently, in all cases TNCs used arguments about their legal rights and obligations, free choice, 'Nanny State' and freedom of intellectual property right, as they had done to oppose food-marketing policy in Chile (60), and reminiscent of the tobacco and alcohol industries' strategies (87). In Chile and Mexico, SSB companies argued against the tax on the basis of the right of free consumption, while in Colombia they applied litigation measures to CSO advertising against consuming SSBs outlining the health risk this implies.…”
Section: Discussionmentioning
confidence: 99%